Perception of banking customers towards the adoption of online banking in Malaysia / Muslimatul Izzati Zakaria - Zakaria, Muslimatul Izzati (Faculty of Business and Management, 2019)
Internet has become one of the needs in today lifestyle. This also has been influenced the banking institution. However, the adoption towards this technology is still limited despite the numerous benefits that the online banking offers to the customers (Estrella-Ramon, Sanchez-Perez & Swinnen, 2016). As for Malaysia, online banking started to develop in the year 2000. The term eBanking used to represent the paperless and internet banking services. The first bank that provides the online banking services was Malayan Bank or also known as Maybank. Maybank maintain its' image as the largest domestic bank in term of asset and also as the network distribution that commands it own portal. This study investigate the perception of banking customers towards the adoption of online banking in Malaysia. The questionnaire distributed to 1 15 banking customers in Malaysia. The questionnaire focusing on the independent variable which are trust, usability, reliability and service quality. Descriptive analysis, reliability and validity tests, and regression analysis will be conducted using SPSS 21 package. The study shows that trust and usability have negative relationship with the perception on adoption of online banking while reliability and service quality show a positive relationship with the dependent variable. The research also suggested that the bank institutions can try to find a way to get the trust from offline banking users to change to online banking.